Doppler sonographic evaluation of mechanical and bioprosthetic mitral valve prostheses during exercise with a rate corrected pressure half time. Issue 6 (June 1992) - Weiss, P; Hoffmann, A; Burckhardt, D
Abstract : OBJECTIVE--To compare the effect of exercise on pressure half time in patients with mechanical or bioprosthetic mitral valves. A relative pressure half time (pressure half time as a percentage of RR interval) was used in an attempt to correct for the shortening of the diastolic time interval caused by the increase in heart rate during exercise and thus to uncover the effects of valve design on pressure half time during exercise. PATIENTS--Twenty clinically stable (New York Heart Association grade I-II) patients with mechanical (n = 12) or bioprosthetic (n = 8) mitral valves (median age 51) years. The median time since valve replacement was 42 months. METHODS--Continuous wave Doppler echocardiography from the apical view at rest and during moderate supine bicycle exercise (50 W). RESULTS--During exercise the mean (SD) heart rate increased from 79 (12) to 101 (12) beats per minute (95% confidence interval (95% CI) of difference, 15 to 29/min) and the peak pressure gradient from 11 (5) to 18 (6) mm Hg (95% CI of difference 5 to 9 mm Hg). The pressure half time decreased from 114 (30) to 78 (26) ms (95% CI of difference (30-42 ms). There was no difference between the valve types. The relative pressure half time remained unchanged in patients with mechanical valves during exercise (13 (4) rest and 13 (5)% exercise, respectively) and decreased in patients with bioprostheses (17 (3) and 12 (3)%, respectively (95% CI of difference 2 to 8%, p = 0.025). CONCLUSIONS--In patients with mechanical mitral valves the decrease in the pressure half time during exercise is probably mostly the result of the shortening of the diastolic time interval with increasing heart rate whereas in patients with bioprosthetic valves an increase in functional valve area may contribute to the shortening of pressure half time during exercise.